2006
DOI: 10.1590/s0074-02762006000800013
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater sponge spicules: a new agent of ocular pathology

Abstract: In a recent outbreak of human ocular injuries that occurred in the town

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Severe eye lesions were observed and described by Volkmer-Ribeiro et al (10) and Volkmer-Ribeiro and Batista (11). Such lesions affected bathers diving with open eyes into the Araguaia River (Araguatins, Tocantins state, Brazil), who came into contact with tiny spicules that cover the gemmules of the species Drulia uruguayensis and Drulia ctenosclera.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Severe eye lesions were observed and described by Volkmer-Ribeiro et al (10) and Volkmer-Ribeiro and Batista (11). Such lesions affected bathers diving with open eyes into the Araguaia River (Araguatins, Tocantins state, Brazil), who came into contact with tiny spicules that cover the gemmules of the species Drulia uruguayensis and Drulia ctenosclera.…”
Section: Introductionmentioning
confidence: 93%
“…Such lesions affected bathers diving with open eyes into the Araguaia River (Araguatins, Tocantins state, Brazil), who came into contact with tiny spicules that cover the gemmules of the species Drulia uruguayensis and Drulia ctenosclera. Those spicules were found during biopsy and surgically removed from the injured eyes (10).…”
Section: Introductionmentioning
confidence: 99%
“…2 Examination consisted of the measurement of visual acuity with charts (tumbling Snellen E or letters), external examination with especial attention to eyelids and bulbar conjunctiva, biomicroscopy of the cornea and anterior segment, intraocular We certify that all applicable institutional and governmental regulations concerning the ethical use of human volunteers were followed during this research.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 We report here the clinical characteristics of this unusual outbreak of eye lesions. We believe that this is the first report of an outbreak of ocular disease because of a foreign body of animal origin.…”
Section: Introductionmentioning
confidence: 91%
“…Especially in rural areas in the SE Region where there are deforestation and residences near natural forest children can be stung by snakes and show clinical complications [149,150]. Clinical researches [140,144] detected important ocular lesions caused by freshwater sponges species Drulia uruguayensis and Drulia ctenosclera, in school age children who swam in some rivers near their homes, in the Brazilian Amazon. These works revealed that freshwater sponge spicules may be a dangerous etiological agent of ocular pathology to kids that swim on those rivers.…”
Section: Children's Environment In Brazil: From Domestic (Indoor) To mentioning
confidence: 99%